PEKAN EDUKASI DAN LITERASI KESEHATAN REPRODUKSI SEBAGAI MEDIA PSIKOEDUKASI PADA REMAJA - Tiara Diah Sosialita (Universitas Mataram, 2022)
Reproductive health problems and risky behavior in the context of adolescents are increasingly being considered worldwide, as the results of the Indonesian Demographic Health Survey (IDHS) reveal that adolescents throughout Indonesia experience sexuality problems. A similar condition is shown by adolescents in the target areas where knowledge of reproductive health and sexual risk behavior is low with a proportion of 10.26% for boys and 10% for girls out of a total of 40 adolescents surveyed. This educational program aims to increase awareness and knowledge of adolescents about reproductive health and risky sexual behavior. Activities in the form of seven (7) online sessions via Instagram Live during 24 July – 8 August 2021 covering material: adolescent sexual behavior, adolescent development, adolescent reproduction, sexually transmitted diseases and HIV/AIDS, early marriage, unwanted pregnancy, and risky behavior. teenager. The results of the activity showed that the target youth (72% girls and 28% boys aged 11-19 years) had adequate awareness and knowledge about reproductive health and the impact of risky behavior. Educational activities were able to increase knowledge of reproductive health in adolescents after the provision of materials with a fairly high effectiveness (ES = 1.45).